2017
DOI: 10.1002/eap.1475
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients influence the thermal ecophysiology of an intertidal macroalga: multiple stressors or multiple drivers?

Abstract: Urbanization of coastlines is leading to increased introduction of nutrients from the terrestrial environment to nearshore habitats. While such nutrient influxes can be detrimental to coastal marine organisms due to increased eutrophication and subsequent reduced oxygen, they could also have positive effects (i.e., increased food availability) on species that are nitrogen-limited such as macroalgae. Nutrient enrichment in this environment thus has the potential to counteract some of the negative impacts of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 112 publications
(289 reference statements)
2
14
0
Order By: Relevance
“…We recognise that changes of 10 °C in a span of 5 h are unlikely to occur in the shallow subtidal system from which we collected Macrocystis, and although this may have contributed to increased physiological stress, the experiments were designed to develop the thermal performance curves (TPCs) of key physiological traits. Other studies have performed thermal ramps of 5 °C per day 81 , 3 °C per three days 82 and some have not performed any thermal acclimation before the start of experiments 56 . In order to make more realistic long-term predictions to climate change (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognise that changes of 10 °C in a span of 5 h are unlikely to occur in the shallow subtidal system from which we collected Macrocystis, and although this may have contributed to increased physiological stress, the experiments were designed to develop the thermal performance curves (TPCs) of key physiological traits. Other studies have performed thermal ramps of 5 °C per day 81 , 3 °C per three days 82 and some have not performed any thermal acclimation before the start of experiments 56 . In order to make more realistic long-term predictions to climate change (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen plays important roles in regulating key enzymatic activities 51 , and is a key regulator of seaweed productivity via direct effects on cell membrane fluidity, protein production, photosynthetic machinery 49,52 , and thermal plasticity 53 . Therefore, nitrogen enrichment might ameliorate the negative effect of high temperature on seaweeds' performance by modulating their photosynthetic and respiratory rates 5,15,[53][54][55][56][57] . However, such positive synergistic effects can be diminished at temperatures that surpass algal thermal thresholds 5,56 , and might vary among species and populations 58 .The giant kelp Macrocystis pyrifera (hereafter, Macrocystis) plays critical functional roles in coastal ecosystems 59 .…”
mentioning
confidence: 99%
“…The latter suggests some capacity of organisms to tolerate environmental change. The prevalence of each interaction is poorly understood as some studies have reported synergistic interactions [4,7], while others have reported additive effects or antagonistic interactions [11][12][13]. Moreover, interactive effects of multiple stressors appear to vary across taxa, developmental stages and trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The 2014–2016 large‐scale extreme MHW in the northeastern Pacific Ocean decimated giant kelp forest ecosystems across California and Baja California, Mexico (Arafeh‐Dalmau et al, 2019; Cavanaugh et al, 2019; Rogers‐Bennett et al, 2019), and we infer that this event compounded the effects of El Niño and contributed to the poor performance of Oregon's intertidal kelps (Figures 10 and 11). Thermal effects were also compounded by associated declines in DIN, which is crucial for photosynthesis and protein production for kelps, and necessary for the increased energetic demands that are associated with warmer than usual temperatures (Colvard & Helmuth, 2017; Gao et al, 2013, 2017; Gerard, 1997; Kremer, 1980; Turpin, 1991; Turpin et al, 1988; Wheeler & North, 1980). As shown here, in 2017, H. sessile , E. menziesii , and P. palmaeformis numbers at Oregon sites increased, particularly at the Southern Cape.…”
Section: Discussionmentioning
confidence: 99%